1996
DOI: 10.1177/002221949602900410
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Schema-Based Instruction on the Mathematical Word-Problem-Solving Performance of Students with Learning Disabilities

Abstract: This study examined the effects of a schema-based direct instruction strategy on the word-problem-solving performance of three third- and fourth-grade students (2 girls, 1 boy) with learning disabilities. An adapted multiple-probe-across-students design was used. Results indicated that the intervention was successful in increasing the percentage of correct solutions to word problems for all 3 students. In addition, maintenance of word-problem solving was seen 2 to 3 weeks after the study. Student interviews in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
111
0
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(137 citation statements)
references
References 17 publications
9
111
0
15
Order By: Relevance
“…Second, findings demonstrate the efficacy of SBI for tutoring AR students on problem types that extend beyond total, difference, and change relationships addressed in prior work (Fuchs et al, in press;Jitendra & Hoff, 1996;Jitendra et al, 1998Jitendra et al, , 2002Xin et al, 2005. By contrast, the problem types addressed in the present study involve multiple quantities of more than one kind of item, halving quantities, step-up functions, and pictograph problems, with emphasis on multi-step problem solving, combining problem types, and ignoring irrelevant information.…”
Section: Discussionsupporting
confidence: 55%
“…Second, findings demonstrate the efficacy of SBI for tutoring AR students on problem types that extend beyond total, difference, and change relationships addressed in prior work (Fuchs et al, in press;Jitendra & Hoff, 1996;Jitendra et al, 1998Jitendra et al, , 2002Xin et al, 2005. By contrast, the problem types addressed in the present study involve multiple quantities of more than one kind of item, halving quantities, step-up functions, and pictograph problems, with emphasis on multi-step problem solving, combining problem types, and ignoring irrelevant information.…”
Section: Discussionsupporting
confidence: 55%
“…Yet, when the question is changed a little bit or students confront with a new question, this approach may fail to solve the problem (Viennot &Moreau, [82] Jitendra &Hoff, [40]; Steele & Johanning, [75]. The readily available solutions mentioned in the short-cut approach are addressed within the scope of procedural knowledge (Anderson, [3]; Byrnes & Wasik, [20], Baroody, Feil, & Johnson, [8].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Schematic representations that can be used to interpret and elaborate on information in the problem lead to enhanced problem solving performance (Pape & Tchoshanov, 2001). Such representations are essential components of many studies of SBI (e.g., Fuchs et al, 2009;Fuchs, Seethaler, et al, 2008;Fuson & Willis, 1989;Griffin & Jitendra, 2008;Jitendra et al, 2009;Jitendra, DiPipi, & Perron-Jones, 2002;Jitendra, Griffin, Deatline-Buchman, & Sczesniak, 2007;Jitendra, Griffin, McGoey, Gardill, Bhat, & Riley, 1998;Jitendra & Hoff, 1996;Jitendra, Hoff, & Beck, 1999;Lewis, 1989;Willis & Fuson, 1988;Xin, 2008;Xin, Jitendra, & Deatline-Buchman, 2005;Xin & SCHEMA-BASED INSTRUCTION 5 Zhang, 2009;Xin, Wiles, & Lin, 2008;Zawaiza & Gerber, 1993). For example, Fuchs, Seethaler, et al (2008) explored the effects of SBI for third graders identified as having mathematics and reading difficulties.…”
Section: Research On Schema-based Instruction and Problem Solvingmentioning
confidence: 99%